Reduced theta-band neural oscillatory activity during affective cognitive control in bipolar I disorder. (February 2023) - Andrews, Carolyn M.; Menkes, Margo W.; Suzuki, Takakuni; Lasagna, Carly A.; Chun, Jinsoo; O'Donnell, Lisa; Grove, Tyler; McInnis, Melvin G.; Deldin, Patricia J.; Tso, Ivy F.
Abstract: Individuals with bipolar I disorder (BD) have difficulty inhibiting context-inappropriate responses. However, neural mechanisms of impaired cognitive control over impulsive behaviors, especially in response to emotion, are unclear. Theta-band neural oscillatory activity over midfrontal areas is thought to reflect cognitive control. The current study examined behavioral performance and theta-band activity during inhibition to affective stimuli in BD, relative to healthy control participants (HC). Sixty-seven participants with BD and 48 HC completed a Go/No-Go task with emotional face stimuli during electroencephalography (EEG) recording. Behavior was measured with reaction time, discriminability ( d' ) and response bias ( β ). Time-frequency decomposition of EEG data was used to extract event-related theta-band (4–7 Hz) neural oscillatory power and inter-trial phase consistency (ITPC) over midline fronto-central areas. Behavior and theta-band activity were compared between groups, while covarying for age. Participants with BD exhibited slower response execution times on correct Go trials and reduced behavioral discrimination of emotional versus neutral faces, compared to HC. Theta-band power and ITPC were reduced in BD relative to HC. Theta-band power was higher on No-Go trials than Go trials. The magnitude of differences in theta-band activity between Go/No-Go trial types did not differ between groups. Increased theta-band power was associated with faster response execution times, greater discrimination of differing facial expressions, and stronger tendency to respond both across the full sample and within the BD group. Attenuated midline fronto-central theta-band activity may contribute to reduced cognitive control and maladaptive behavioral responding to emotional cues in individuals with BD.